Outcomes in patients with sarcoidosis and COVID-19 - Nadeem, Owais; Sharma, Amreeta; Alaouie, Diana; Bradley, Patrick; Ouellette, Dan; Fadel, Raef; Suleyman, Geehan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: The effect of COVID-19 in patients with sarcoidosis has not been fully explored. The aim was to conduct a retrospective cohort study investigating outcomes in patients with sarcoidosis who were hospitalized with COVID-19. Methods: We included patients who had diagnoses of sarcoidosis and COVID-19 between January 1, 2020, and February 28, 2021. Primary outcomes included development of critical COVID-19; need for supplemental oxygen, noninvasive ventilation, and invasive ventilation; and death. Association of comorbidities and immunosuppression therapy with outcomes were analyzed. Multiple logistic regression analysis was used to assess risk factors associated with critical COVID-19. Results: Of 1198 patients with COVID-19, 169 had sarcoidosis (14.1%) and 1029 (85.9%) did not (control group). Of the 169 patients with sarcoidosis and COVID-19, 84 (49.7%) were hospitalized (study group: mean age 62.4 years; 61.9% women; and 56.0% Black). The study group required supplemental oxygen (81% vs 62%; p = 0.001) and noninvasive ventilation (33.3% vs 6.4%; p < 0.001) more often and had lower mortality (15.5% vs. 30.4%; p = 0.004) than the control group. In patients hospitalized with COVID-19, sarcoidosis was not associated with critical COVID-19 (odds ratio, 0.77; 95% CI, 0.46-1.29; p = 0.317), but having sarcoidosis while taking immunosuppression therapy was associated with decreased risk of critical COVID-19 (odds ratio, 0.45; 95% CI, 0.31-0.65; p < 0.001). Conclusions: Patients with sarcoidosis may not be at increased risk of critical illness or death from COVID-19, and immunosuppression therapy in these patients may reduce the risk of critical COVID-19.